2023
DOI: 10.4314/gjpas.v29i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Dynamics And Physicochemical Parameters In A Tropical Estuary: Qua-Iboe River Estuary, Southeast Coast Of Nigeria

Emeka V I,
Emeka C N,
Ebong E D
et al.

Abstract: Estuaries are important ecosystems that support biodiversity and influence the economy of the regions they occupy. Major physicochemical variables of Qua-Iboe River estuary in the Niger Delta region of Nigeria were assessed for ecosystem quality. The influence of tidal current on the spatial distribution of physicochemical parameters in the estuary was examined. Physicochemical parameters, including transparency, temperature, salinity, dissolved oxygen, density and pH were measured in-situ during the dry seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…By their results, Qua-Iboe River was classified as a partially mixed estuary. Emeka et al (2023b) studied the spatial distribution of bottom water physicochemical parameters of the Cross River estuary, with data obtained in the rainy season of 2012. They observed that salinity maximum, minimum and mean, within the channel were, 0.2 ‰, 0.15 ‰, and 0.16 ‰, with values increasing in the downstream direction.…”
Section: Introductionmentioning
confidence: 99%
“…By their results, Qua-Iboe River was classified as a partially mixed estuary. Emeka et al (2023b) studied the spatial distribution of bottom water physicochemical parameters of the Cross River estuary, with data obtained in the rainy season of 2012. They observed that salinity maximum, minimum and mean, within the channel were, 0.2 ‰, 0.15 ‰, and 0.16 ‰, with values increasing in the downstream direction.…”
Section: Introductionmentioning
confidence: 99%